2013 IEEE/ACM International Conference on Computer-Aided Design (ICCAD) 2013
DOI: 10.1109/iccad.2013.6691116
|View full text |Cite
|
Sign up to set email alerts
|

Constrained pattern assignment for standard cell based triple patterning lithography

Abstract: Triple patterning lithography (TPL) has been recognized as one of the most promising candidates for 14/10nm technology node. Apart from obtaining legal TPL decompositions, various concerns have been raised by the designers, among them consistently assigning the same pattern for the same type of standard cells and balancing the usage of the three masks are two most critical ones. In this paper, a hybrid approach (SAT followed by a sliding-window approach) is proposed targeting at these two problems. To assign t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The experimental results show that our approach is not only effective but also efficient as compared with a state-of-the-art TPL-aware placer. In the future, we will investigate how to extend or modify our approach to handle the presence of a subset of precolored cells and the requirement of assigning the same coloring solution to cell instances of the same type during detailed placement [18], [19]. We will be also interested in looking into how to take layout decomposition into account at placement stages, including global placement, legalization, and detailed placement, to help further improve the quality of placement.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The experimental results show that our approach is not only effective but also efficient as compared with a state-of-the-art TPL-aware placer. In the future, we will investigate how to extend or modify our approach to handle the presence of a subset of precolored cells and the requirement of assigning the same coloring solution to cell instances of the same type during detailed placement [18], [19]. We will be also interested in looking into how to take layout decomposition into account at placement stages, including global placement, legalization, and detailed placement, to help further improve the quality of placement.…”
Section: Discussionmentioning
confidence: 96%
“…From the aspect of layout design, existing research results have focused more on TPL layout decomposition [14], [17], [18], [20], [23], [25] and TPL-aware routing [16], [22] while very few works have been reported for TPL-aware placement [19], [24]. Although the TPL layout decomposition problem is NP-hard for general layouts [25], it has been recently shown that for any standard-cell-based row-structure layout, whether a TPL decomposition solution that has no coloring conflict and no stitch insertion exists for the M1 layer can be exactly determined in polynomial time [20].…”
Section: Introductionmentioning
confidence: 99%
“…LELELE type TPL technology [8][9][10][11][12][13][14][15][16][17][18] in which litho-etch process is repeated three times is often discussed in literature. However, it suffers from native conflict and overlay problems.…”
Section: Introductionmentioning
confidence: 99%
“…Triple patterning lithography (TPL) is one of the most promising techniques in the 14 nm logic node and beyond. In order to realize a target pattern, various types of techniques including design for manufacturability, such as LELE type double patterning lithograph [1][2][3][4][5][6][7], LELELE type TPL [8][9][10][11][12][13][14][15][16][17][18], LELECUT type TPL [19], and side wall process [20], are used in addition to a basic litho-etch process with optimized mask. These techniques are summarized in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Ghaida et al [17] reused the double patterning techniques. For row-based layout design, Tian et al [19], [21] presented polynomial time decomposition algorithms.…”
mentioning
confidence: 99%